2017
DOI: 10.22159/ijap.2017.v9s1.22_27
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Physical Stability Test of Griseofulvin Microemulsion Gel

Abstract: Objective: The main objective of this research is to make and evaluate the formulation of a griseofulvin microemulsion gel for topical use to increase the solubility and safety of the drug. Methods:The optimized microemulsion formula contains 5% oleic acid as the oil phase, 25% Tween 80 as the surfactant, and 20% ethanol (96%) as the cosurfactant.Results: Organoleptic observations of the microemulsion showed that it had a clear and transparent yellowish color, while the microemulsion gel had a hazy yellowish c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 4 publications
0
21
0
6
Order By: Relevance
“…Stability studies were carried out for the formulation of snakehead fish powder, the double emulsion as per ICH guidelines at 40±4 °C. Thermodynamic stability of prepared double emulsion formulation was assessed by stability under centrifugation and Freeze-Thaw cycles [12,17].…”
Section: Stability Studymentioning
confidence: 99%
“…Stability studies were carried out for the formulation of snakehead fish powder, the double emulsion as per ICH guidelines at 40±4 °C. Thermodynamic stability of prepared double emulsion formulation was assessed by stability under centrifugation and Freeze-Thaw cycles [12,17].…”
Section: Stability Studymentioning
confidence: 99%
“…The physical appearance of ZOL gel emulsion during the storage at 25°C showed that the formulation was stable and homogenous till day 28. The consistency and color of the gel emulsion were smooth and did not exhibit phase separation before or after the addition of the gelling agent, showing that the gel emulsion was stable [21]. Its color, taste, and odor were also acceptable.…”
Section: Discussionmentioning
confidence: 98%
“…Owen et al reported that an increase in storage temperature also increases the apparent viscosity [25]. In addition, Iradhati and Juhfri noted that globule flocculation could increase the viscosity during the preparation of ZOL gel emulsion [21]. The fluctuation in the viscosity values on day 14 at 40°C storage and day 14 at 25°C storage might be caused by syneresis, the discharge of the entangled fluid in the gel emulsion to the surface [27].…”
Section: Discussionmentioning
confidence: 99%
“…The viscosity values at each rpm like 5, 10, 20, 50, 100 were noted. For the same gel sample, the experiment was repeated thrice, and the average reading was recorded (Andrews, 2009;Iradhati and Jufri, 2017).…”
Section: Viscositymentioning
confidence: 99%